Efektivitas Temu Kunci (Boesenbergia rotunda) Terhadap Penurunan Kadar Formalin Pada Ikan Tuna (Thunnus sp.): Effectiveness of Key Gathering (Boesenbergia rotunda) Against Reduction of Formalin Levels in Tuna (Thunnus sp.) - Zamhariroh, Zamhariroh; Hanum, Galuh Ratmana (Medicra (Journal of Medical Laboratory Science/Technology), 2018)
Tuna as a marine fish that has an exceptional potential to be the mainstay of Indonesia. The high demand for tuna makes a great opportunity for Indonesia as a producer in the export of these products. Related to this condition, the producers have come up with a variety of ways to keep the fish appear fresh by way of preservation, one of them is by using formalin. Finger root plants have active compounds that can reduce formalin in tuna saponins. This study used tuna fish that had been soaked with a solution containing 10% formalin. The research was conducted at Surabaya City Health Office. Formalin content was measured using the spectrophotometer method. Parameters used were formalin content. The results of this study indicate that the concentration of key solution and storage duration significantly influence at 50% concentration for 5 days is the most effective concentration and duration of immersion with an average yield of 0,04 mg/l.